Innovative ways of making aid effective in Ghana: Tied aid versus direct budgetary support - Peter Quartey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
There has been significant amount of aid inflows to developing countries including Ghana, but these have been very volatile. Aid flows have been associated with low domestic resource mobilization and have reduced Ghana to a country heavily dependent on aid. The amount of official development assistance (ODA) inflows has fallen in recent years and has become unpredictable. It is general knowledge that aid has not yielded the desired benefit. In an attempt to improve aid effectiveness donors have used tied aid not just to promote commercial interests but also to target aid to particular projects that have direct links with poverty. However, this has not yielded the maximum benefits required. Recently, the government of Ghana and its development partners agreed on an aid package dubbed the multi-donor budgetary support (MDBS), which would ensure continuous flow of aid to finance the government's poverty related expenditures. This paper examines the MDBS, with special focus on how it overcomes the problems of tied aid and other project support. It concludes that the MDBS is innovative and could work in Ghana, but it would need trust and a well-designed, coordinated effort on the part of the government of Ghana and its development partners. Second, its effectiveness would depend crucially on measures to help reduce the debt burden, so that the government would not be compelled to use aid inflows to service its debt. Finally, the MDBS could be more effective if it did not have to operate alongside other project support.
Keywords: F21; F34; F35; 330; multi-donor budgetary support; tied aid; poverty reduction; Entwicklungshilfe; Entwicklungshilfekonditionen; Ghana